A superhydrophobic surface with aging resistance, excellent mechanical restorablity and droplet bounce properties. Issue 23 (5th June 2020) - Wang, Guangfei; Zhou, Jin; Wang, Meimei; Zhang, Yanbin; Zhang, Yong; He, Qiang
Abstract : Superhydrophobic silicone rubber materials have special microstructures and show excellent mechanical properties. Abstract : The use of a silicone rubber composite insulator has become an important aspect to ensure the safe operation of an electrical power grid. This study introduces a preparation method of a superhydrophobic silicone rubber surface using a simple preparation process at low cost and with excellent performance, which can be used in the mass production of silicone rubber composite insulators. In this study, the combination of a compression molding process and a template method was used to prepare the product. A microstructure composed of numerous boat-shaped grooves was constructed on the surface of silicone rubber. The modification of a low surface energy material is not required. The static contact angle with water after the high-temperature treatment exceeds 150°, and the rolling angle is under 10°. Excellent performance has been observed in terms of self-cleaning effect, aging resistance, and mechanical and droplet bounce properties. It has been shown that the loss of superhydrophobic properties, due to the prolonged immersion in water, can be restored by a high temperature heating process.